Trend Ratio Analysis on Banking Companies Listed in LQ45 Period of 2009 - 2013 - Aditya, Stefanus Reinhard; Noveria, Ana (Journal of Business and Management, 2015)
Abstract. Every company needs a strategy designed to achieve the vision and objectives of the company, which must be appropriated to the demands of the existing business environment. One of the strategy that must be considered by company is the effort to attract investors.This research focuses on the trend of each financial ratio analysis, calculation of financial ratios investors processed in accordance with existing formulations, i.e: capital adequacy ratio (CAR), cost to income (CIR), net income margin (NIM), non performing loan (NPL), loan to deposit ratio (LDR), and return on asset (ROA). Making conclusion taken from the result of the analysis, based on the analysis, conclusion be obtained from testing expertâ€™s theory with researcher allegation along with facts on the field. Each of the financial ratios that have been calculated will determine the year base as basis of comparison and given the index number 100. Population of this research are all banking companies listed in Indonesia Stock Exchange. Purposive sampling used as the sampling technique, using random type of sample selection with certain consideration to be sample. As of the consideration, the company must be listed in Indonesia Stock Exchange period of 2009 â€“ 2013, and listed five years respectively in LQ45 index. With the result are Bank Central Asia, Tbk, Bank Rakyat Indonesia (Persero), Tbk, Bank Danamon Indonesia, Tbk, and Bank Mandiri (Persero), Tbk.After forecasting using trend analysis (time series analysis) then the result are as follows, in 2014 and 2015 company with highest CAR prediction is Bank Rakyat Indonesia. While the highest CIR, NIM, and LDR prediction is Bank Central Asia, Tbk. For the highest ROA and NPL prediction is Bank Danamon Indonesia, Tbk.Keywords : Banking, Financial Ratio AnalysisÂ